INVESTIGATION OF MECHANICAL PROPERTIES OF HIGH-PERFORMANCE LIGHTWEIGHT CONCRETE WITH PUMICE AGGREGATE - Tunç, Esra Tuğrul; Alyamaç, Kürşat Esat; İnce, Ragıp; Ulucan, Zülfü Çınar (E-Journal of New World Sciences Academy, 2018)
Traditional concretes, which have a lot of usage in practice, have huge unit weights. Lightweight concretes have less weight than traditional concretes. By using lightweight concrete in the reinforced concrete structures, the total amount of concrete to be used in the buildings can be reduced, the buildings can be lightened, and the total weight of the building can be reduced. High-performance concrete is needed to build permanent and long-lasting structures. The aim of this study is to assess comprehensively the previous studies on highstrength lightweight concrete and to present a different perspective for this subject. In the present study, the mechanical properties of high-performance lightweight concretes with different mixing ratios were examined. Compressive strengths of traditional concretes and lightweight concretes were compared. In addition, the compressive strengths of the concrete specimens produced in the building materials laboratory were tried to be estimated by the statistical analysis. A good fitting was obtained between the experimental and the predicted results.

Traditional concretes, which have a lot of usage in practice, have huge unit weights. Lightweight concretes have less weight than traditional concretes. By using lightweight concrete in the reinforced concrete structures, the total amount of concrete to be used in the buildings can be reduced, the buildings can be lightened, and the total weight of the building can be reduced. High-performance concrete is needed to build permanent and long-lasting structures. The aim of this study is to assess comprehensively the previous studies on high-strength lightweight concrete and to present a different perspective for this subject. In the present study, the mechanical properties of high-performance lightweight concretes with different mixing ratios were examined. Compressive strengths of traditional concretes and lightweight concretes were compared. In addition, the compressive strengths of the concrete specimens produced in the building materials laboratory were tried to be estimated by the statistical analysis. A good fitting was obtained between the experimental and the predicted results.
INVESTIGATION OF MECHANICAL PROPERTIES OF HIGH-PERFORMANCE LIGHTWEIGHT CONCRETE WITH PUMICE AGGREGATE
Keywords: Engineering; Mühendislik